There's something out there waiting for us: drones with thermal cameras as revolutionary tools in population monitoring - Guimarães, Camila Rezende (2023)
Population monitoring is crucial for the conservation of endangered species, but the most commonly used methods are time-consuming and resource-intensive. This work proposes the use of drones equipped with thermal and RGB sensors (color sensors) for population monitoring of the southern muriqui (Brachyteles arachnoides) as an alternative tool in challenging study areas. We tested the effect of sunlight and period of day on detection efficiency and detection distance for a better data collection design. Our results pointed to an effect of sunlight on detection efficiency, but not on detection distance. Considering the period of day, we found no effect on our results. The work also presents our methodology and results in population monitoring with drones in Serra da Mantiqueira and Serra do Mar. We suspect that there are 3 social groups of muriquis that use the study area in the Serra da Mantiqueira at a minimum counting of 39 individuals in just one flight. In the Serra do Mar we recorded 1 social group of muriquis with a minimum count of 10 individuals that use the surroundings of the study area and can use the inside area of the property. Also, by analyzing the high quality images generated by the drone, it was possible to make a sex and age classification of 19 and 6 individuals in Serra da Mantiqueira and Serra do Mar respectively. Moreover we discuss here the limitations that still exist regarding the use of this technology and possible future ways to make it even more efficient in population monitoring and in other areas of study. Keywords: Brachyteles arachnoides. UAV. Primates. Endangered Species. Population Monitoring.